Obrona z urzędu w stadium wykonawczym w świetle projektu ustawy z dnia 27 września 2013 r. o zmianie ustawy — Kodeks postępowania karnego oraz niektórych innych ustaw - Chabier, Patrycja (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article raises the issue of influence of the proposed changes of the Code of Criminal Procedure on the Executive Criminal Code with regard to public defence for sentenced persons. According to the current regulation, a sentenced person can defend themselves in person or through legal assistance of his own choice or, if they do not have sufficient means to pay for legal assistance, to be given it free. The author notes that the proposal of penal procedure reform will automatically change through the use of Article 1 para. 2 of the Executive Criminal Code the executive procedure. Sentenced persons will therefore not be obliged to prove their indigence to receive a public defender. They will only need to submit a simple application for a public defender without any further explanations. The only difficulty may be an application fee in the amount of 600 PLN. Having regard to the approval by the Sejm of the Republic of Poland of the revision of the abovementioned law on 30 August 2013, the Marshal of the Sejm submitted an adopted bill to the President of the Republic of Poland for signature. The amendment is expected to enter into force at the beginning of July 2015.
Keywords: kodeks karny wykonawczy; kodeks postępowania karnego; nowelizacja kodeksu karnego; pomoc prawna; obrońca z urzędu; analiza